Polycystic ovary syndrome: insight into pathogenesis and a common association with insulin resistance - Barber, Thomas M (Clin Med (Lond), 2016)
Polycystic ovary syndrome (PCOS) is a common condition that typically develops in reproductive-age women. The cardinal clinical and biochemical characteristics of PCOS include reproductive dysfunction and hyperandrogenic features. PCOS is also strongly associated with obesity based on data from epidemiological and genetic studies. Accordingly, PCOS often becomes manifest in those women who carry a genetic predisposition to its development, and who also gain weight. The role of weight gain and obesity in the development of PCOS is mediated at least in part, through worsening of insulin resistance. Compensatory hyperinsulinaemia that develops in this context disrupts ovarian function, with enhanced androgen production and arrest of ovarian follicular development. Insulin resistance also contributes to the strong association of PCOS with adverse metabolic risk, including dysglycaemia, dyslipidaemia and fatty liver. Conversely, modest weight loss of just 5% body weight with improvement in insulin sensitivity, frequently results in clinically meaningful improvements in hyperandrogenic, reproductive and metabolic features. Future developments of novel therapies for obese women with PCOS should focus on promotion of weight loss and improvement in insulin sensitivity. In this context, therapies that complement lifestyle changes such as dietary modification and exercise, particularly during the maintenance phase of weight loss are important. Putative novel targets for therapy in PCOS include human brown adipose tissue.